Accelerated Development of the First-Order Central Auditory Neurons With Spontaneous Activity - Yin, Xin-Lu; Jie, Hui-Qun; Liang, Min; Gong, Li-Na; Liu, Han-Wei; Pan, Hao-Lai; Xing, Ya-Zhi; Shi, Hai-Bo; Li, Chun-Yan; Wang, Lu-Yang; Yin, Shan-Kai (Frontiers in Molecular Neuroscience, 2018)
In developing sensory systems, elaborate morphological connectivity between peripheral cells and first-order central neurons emerges via genetic programming before the onset of sensory activities. However, how the first-order central neurons acquire the capacity to interface with peripheral cells remains elusive. By making patch-clamp recordings from mouse brainstem slices, we found that a subset of neurons in the cochlear nuclei, the first central station to receive peripheral acoustic impulses, exhibits spontaneous firings (SFs) as early as at birth, and the fraction of such neurons increase during the prehearing period. SFs are reduced but not eliminated by a cocktail of blockers for excitatory and inhibitory synaptic inputs, implicating the involvementof intrinsic pacemaker channels. Furthermore, we demonstrate that these intrinsic firings (IFs) are largely driven by hyperpolarization- and cyclic nucleotide-gated channel (HCN) mediated currents (Ih), as evidenced by their attenuation in the presence of HCN blockers or in neurons from HCN1 knockout mice. Interestingly, genetic deletion of HCN1 cannot be fully compensated by other pacemaker conductances and precludes age-dependent upregulation in the fraction of spontaneous active neurons and their firing rate. Surprisingly, neurons with SFs show accelerated development in excitability, spike waveform and firing pattern as well as synaptic pruning towards mature phenotypes compared tothose without SFs. Our results imply that SFs of the first-order central neurons may reciprocally promote their wiring and firing with peripheral inputs, potentially enabling the correlated activity and crosstalk between the developing brain and external environment.